Community participation enhanced prenatal mental health through strengthening peers’ support and partners’ communication in Chinese mothers: A cross-sectional study - Shanshan An; Sheng Sun (PLoS ONE, 2025)
This study investigated the relationship between extensive community participation and prenatal mental health, focusing specifically on the mediating roles of peer support and partner communication. A cross-sectional survey was conducted in Jiangsu, China, involving 1,705 pregnant participants. Structural Equation Modeling was employed to examine how offline peer support, online peer support, and partner communication mediate the association between community participation and prenatal mental health. Among the 1,705 participants (Mean age = 29.57, SD age = 3.70, Max age = 43, Min age = 16), 1,000 (58.7%) were giving birth for the first time, and 975 (57.3%) were local residents. The mean score for community participation was 4.43, while that for prenatal mental health was 4.21. These findings indicate that extensive community participation does not directly affect prenatal mental health. Instead, peer support and partner communication serve as parallel mediators, while social media and partner communication function as sequential (chain) mediators. These results underscore the critical need to enhance both the quantity and quality of partner-centered maternal support networks by leveraging peer groups and digital platforms. Strengthening these relational pathways can facilitate more effective communication between partners and ultimately contribute to improved maternal mental health during pregnancy.